Some Kinematically Admissible Velocity Fields in Multimaterial Extrusion - Mishuris, G.S.; Śliwa, R.E. (Engineering Transactions, 2015)
Two different models of flow fields are proposed to describe plastic deformations during the extrusion of multi-metal composites. To construct the presented kinematically admissible flow fields, some information is adopted from experimental works concerning extrusion of longitudially oriented metal composites. Formulae for velocities, strain-rate tensor and deviator of stresses are found.